Assessment of Genetic Variability, Character Association and Path Coefficient Analysis in Gomphrena (Gomphrena globosa L.) Genotypes for Productivity and Quality Traits - Nagajyothi, G. N.; Balaji, S. K.; Satish, D.; Sateesh, R. P. (International Journal of Bio-resource and Stress Management, 2025)
An experiment was conducted during November 2021–March, 2022 at the experimental block of Floriculture and Landscape Architecture, College of Horticulture, Bagalkot, Karnataka, India using thirteen different Gomphrena (Gomphrena globosa L.) genotypes under randomized block design to determine the extent of genetic variability. The phenotypic coefficient of variation (PCV) was higher than genotypic coefficient coefficient of variation (GCV) for all growth, flowering, yield and quality traits under study. Higher GCV and PCV was observed for number of leaves plant-1, moderate for plant height, number of secondary branches, stem girth, days to bud initiation, inflorescence length, individual flower weight, number of flowers plant-1, yield plant-1 and shelf life. High heritability combined with high genetic advance over mean was recorded for plant height, secondary branches, number of leaves, stem girth, days to bud initiation, inflorescence length, individual flower weight, number of flowers and yield plant-1. The flower yield plant-1 had significantly positive association with plant height, plant spread in N-S and E-W direction, number of primary and secondary branches, number of leaves, stem girth, duration of flowering, stalk length, inflorescence length, flower diameter, number of flowers plant-1 and individual flower weight. The character association studies revealed that, flower yield plant-1 had direct and positive association with plant spread, stem girth, number of secondary branches, individual flower weight, diameter of flower, inflorescence length, stalk length, days to flowering, bud initiation, number of leaves and plant height.